Increased Catecholamine Levels and Inflammatory Mediators Alter Barrier Properties of Brain Microvascular Endothelial Cells in vitro - Ittner, Cora; Burek, Malgorzata; Störk, Stefan; Nagai, Michiaki; Förster, Carola Y. (Frontiers in Cardiovascular Medicine, 2020)
Recent studies have suggested a pathogenetic link between ischemic stroke and Takotsubo cardiomyopathy (TCM) with poor outcome, when occurring simultaneously. Increased catecholamine (CAT) levels as well as elevated inflammatory mediators (INF) are found in the blood of patients with ischemic stroke concomitant with Takotsubo syndrome (TTS). On molecular level, the impact of these stressors combined with hypoxemia could compromise the integrity of the blood brain barrier (BBB) resulting in poor outcomes. As a first step in the direction of investigating possible molecular mechanisms, an in vitro model of the described pathological constellation was designed. An immortalized murine microvascular endothelial cell line from the cerebral cortex (cEND) was used as an established in vitro model of the BBB. cEND cells were treated with supraphysiological concentrations of CAT (dopamine, norepinephrine, epinephrine) and INF (TNF-α and Interleukin-6). Simultaneously, cells were exposed to oxygen glucose deprivation (OGD) as an established in vitro model of ischemic stroke with/ without subsequent reoxygenation. We investigated the impact on cell morphology and cell number by immunofluorescence staining. Furthermore, alterations of selected tight and adherens junction proteins forming paracellular barrier as well as integrins mediating cell-matrix adhesion were determined by RT-PCR and/or Western Blot technique. Especially by choosing this wide range of targets, we give a detailed overview of molecular changes leading to compromised barrier properties. Our data show that the proteins forming the BBB and the cell count are clearly influenced by CAT and INF applied under OGD conditions. Most of the investigated proteins are downregulated, so a negative impact on barrier integrity can be assumed. The structures affected by treatment with CAT and INF are potential targets for future therapies in ischemic stroke and TTS.